Ankle dorsiflexion range of motion and landing postures during a soccer-specific task - Akbari, H.; Shimokochi, Y.; Sheikhi, B. (PLOS ONE, 2023)
Introduction Ankle dorsiflexion range of motion (DF-ROM) has been shown to be associated with poor landing posture. However, previously used tasks have been controlled, and it is unclear whether clinical measurements of the ankle DF-ROM, are associated with landing positions during sport-specific task. This study sought to determine the relationship between ankle DF-ROM and landing positions. Methods Thirty male soccer players participated in this study. The ankle DF-ROM was measured by the weight bearing lunge test in degrees using a cell phone app (TiltMeter). Landing patterns were assessed during a soccer-specific task using landing error scoring system items using Kinovea software. Simple correlations were used to evaluate the relationships between ankle DF-ROM and landing error scores. Results Significant correlations were found between ankle DF-ROM and landing errors (r = -0.450, P = 0.006). A decreased ankle DF-ROM was associated with greater landing errors in a soccer specific situation. Conclusion These results suggest that ankle DF-ROM may serve a useful clinical measure for identifying poor landing posture in the real-world environment. Therefore, assessment of ankle DF-ROM could be included in the screening process, which could help identify the cause of the faulty motion.